1 3 + 3 3 + 5 3 + 7 3 + ⋯ + ( 2 n − 1 ) 3 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yeah same way ... Nice solution..
Since options are given,just put n=1
Yeah this approach is good from examination point of view but for improving the skills we need to get exact approach . but anyways nice solution
N=1 will eliminate 4 out of the 5 possible answers. Even knowing how to solve the question "properly", this is the easiest and thus correct way.
m = 1 ∑ n ( 2 m − 1 ) 3 m = 1 ∑ n ( 8 m 3 − 1 − 3 ⋅ 2 m ⋅ 1 ( 2 m − 1 ) ) m = 1 ∑ n ( 8 m 3 − 1 2 m 2 + 6 m − 1 ) = 8 ( 6 n ( n + 1 ) ) 2 − 1 2 ( 6 n ( n + 1 ) ( 2 n + 1 ) ) + 6 ( 2 n ( n + 1 ) ) − n 2 n 2 ( n + 1 ) 2 − 2 n ( n + 1 ) ( 2 n + 1 ) + 3 n ( n + 1 ) − n n ( n + 1 ) [ 2 n ( n + 1 ) − 2 ( 2 n + 1 ) + 3 ] − n n ( n + 1 ) ( 2 n 2 − 2 n + 1 ) − n n [ ( n + 1 ) ( 2 n 2 − 2 n + 1 ) − 1 ] n ( 2 n 3 − n ) = n 2 ( 2 n 2 − 1 )
After plodding through all of the calculations, we arrived at the answer.
Is there an alternative interpretation which allows us to find the answer immediately? (No idea if this is true). For example, if we wanted to calculate 1 + 3 + 5 + … + ( 2 n − 1 ) , we could compare it to successively building up squares.
Problem Loading...
Note Loading...
Set Loading...
Let the given expression be S , then we have:
S = 1 3 + 3 3 + 5 3 + 7 3 + . . . + ( 2 n − 1 ) 3 = 1 3 + 2 3 + 3 3 + 4 3 + . . . + ( 2 n − 1 ) 3 − 2 3 − 4 3 − 6 3 − 8 3 − . . . − ( 2 n − 2 ) 3 = 1 3 + 2 3 + 3 3 + 4 3 + . . . + ( 2 n − 1 ) 3 − 2 3 ( 1 3 + 2 3 + 3 3 + 4 3 + . . . + ( n − 1 ) 3 ) = k = 1 ∑ 2 n − 1 k 3 − 8 k = 1 ∑ n − 1 k 3 = ( 2 ( 2 n − 1 ) ( 2 n ) ) 2 − 8 ( 2 ( n − 1 ) ( n ) ) 2 = n 2 ( 2 n − 1 ) 2 − 2 n 2 ( n − 1 ) 2 = n 2 ( 4 n 2 − 4 n + 1 ) − 2 n 2 ( n 2 − 2 n + 1 ) = n 2 ( 2 n 2 − 1 )